Novel criteria for intratumoral budding with prognostic relevance for colon cancer and its histological subtypes - Pour Farid, Pantea; Eckstein, Markus; Merkel, Susanne; Grützmann, Robert; Hartmann, Arndt; Bruns, Volker; Benz, Michaela; Schneider-Stock, Regine; Geppert, Carol-Immanuel (International Journal of Molecular Sciences, 2021)
Peritumoral budding and intratumoral budding (ITB) are important prognostic factors for colorectal cancer patients. Scientists worldwide have investigated the role of budding in tumor progression and its prognosis, but guidelines for reliably identifying tumor buds based on morphology are lacking. In this study, next-generation tissue microarray (ngTMA® ) construction was used for tumor bud evaluation, and highly detailed rule-out annotation was used for tumor definition in pancytokeratin-stained tissue sections. Initially, tissues of 245 colon cancer patients were evaluated with high interobserver reliability, and a concordance of 96% was achieved. It was shown that high ITB scores were associated with poor distant metastasis-free survival (p = 0.006 with a cut-off of ≥10 buds). This cut-off was defined as the best maximum value from one of two/three ngTMA® cores (0.6 mm diameter). ITB in 30 cases of mucinous, medullary, and signet ring cell carcinoma was analyzed for the subsequent determination of differences in tumor bud analyses between those subtypes. In conclusion, blinded randomized punched cores in the tumor center can be useful for ITB detection. It can be assumed that this method is suitable for its adoption in clinical routines.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Histological subtypes; Immunohistochemistry; Medullary carcinoma; Metastasis; Mucinous carcinoma; Next-generation tissue microarray analysis; Prognostic biomarker; Signet ring cell carcinoma; Survival analysis; Tumor budding